Conversion of carbon dioxide in low-pressure plasma - Dudin, S.V.; Dakhov, A.N. (Вопросы атомной науки и техники, 2018)
The paper reports the results of experimental study of efficiency of carbon dioxide conversion to CO and O₂ in gas-discharge plasma at low gas pressure. The inductively coupled plasma source operates at 13.56 MHz in the RF power range 5…500 W. Pure CO₂ at pressure of 1…100 mTorr is fed into the plasma while the internal composition of atomic and molecular species is estimated using optical emission spectroscopy. Using the mass spectrometry method, the dependencies of the conversion rate and the energy efficiency of carbon dioxide conversion on the gas pressure and the power deposited in the discharge was measured. The maximum achieved conversion rate is 82 %, while the energy conversion efficiency is up to 50 %.